2009
DOI: 10.1158/1078-0432.ccr-09-0311
|View full text |Cite
|
Sign up to set email alerts
|

Copper Transporter 2 Regulates the Cellular Accumulation and Cytotoxicity of Cisplatin and Carboplatin

Abstract: Purpose: Copper transporter 2 (CTR2) is known to mediate the uptake of Cu +1 by mammalian cells. Several other Cu transporters, including the influx transporter CTR1 and the two efflux transporters ATP7A and ATP7B, also regulate sensitivity to the platinum-containing drugs. We sought to determine the effect of CTR2 on influx, intracellular trafficking, and efflux of cisplatin and carboplatin. Experimental Design: The role of CTR2 was examined by knocking down CTR2 expression in an isogenic pair of mouse embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 35 publications
1
104
0
2
Order By: Relevance
“…The samples were then diluted with aqua regia (4% v/v), and the platinum concentration was measured by inductively coupled plasma mass spectroscopy analysis. To detect the concentration of DNA-platinum adducts, genomic DNA was isolated from the cell lines by methods previously described (14).…”
Section: Antibodymentioning
confidence: 99%
“…The samples were then diluted with aqua regia (4% v/v), and the platinum concentration was measured by inductively coupled plasma mass spectroscopy analysis. To detect the concentration of DNA-platinum adducts, genomic DNA was isolated from the cell lines by methods previously described (14).…”
Section: Antibodymentioning
confidence: 99%
“…[14][15][16][17] Although some groups report distinct molecular behaviors of the different members of the hCTR family, which appear to be cell-dependent, all reports agree that copper, due to its affinity with the hCTR receptor, affects receptormediated entry of cDDP negatively, resulting in improved cytotoxicity. 9,[18][19][20][21][22][23] Although copper receptors have a critical role in the uptake of cisplatin, one of the first studies that focused on the mechanisms of thermal enhancement of cDDP reported an increase in cell membrane fluidity, which in turn augmented the uptake of cDDP. 17,24,25 Therefore, the synergism of cDDP and hyperthermic treatment can potentially be explained in the context of membrane fluidity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][19][20][21][22][23][24] It is widely accepted as the primary mechanism of influx of this platinum-based drug in cells. 10,11 To assess the effect of extracellular copper on this form of drug transport, the surviving fraction and viability ratio of Caco-2 cells was studied by exposing cells to a mixture of 5 µM copper and increasing concentrations of cDDP for 2.5 hours.…”
mentioning
confidence: 99%
“…CTR1 and CTR2 regulate uptake, whereas ATP7A and ATP7B are involved in intracellular sequestration and drug export. Chaperones such as ATOX1 may transport the drugs between intracellular sites (Holzer et al, 2003;Samimi et al, 2004a;Safaei et al, 2007;Blair et al, 2009).…”
Section: Introductionmentioning
confidence: 99%